John Stuart Mill on education and progress - Silva, Elisabete Mendes (2017)
Money-getting, mechanical progress and human happiness lay at the basis of a utilitarian conception of education in Industrial Britain. “The Benthamic or utilitarian propagandism of that time” (Mill, 1981, p. 105) accounted for the happiness of people at the greatest number possible, even if it implied a mechanical and inadequate instruction. Popular education in the first half of the nineteenth century was not only scarce in quantity, but it was also deficient in quality. John Stuart Mill, the paladin for the provision of state education at a national scale in Victorian England, believed education was a means to foster human mind development as well as it accounted for the future progress of mankind. Mill, a utilitarian and empiricist philosopher and political liberal thinker, unlike Bentham and his father James Mill, believed the state should control education therefore guaranteeing its quality and not only quantity. The reforms in education throughout the nineteenth century accompanied the discussion of what should be included in the curriculum of school or university studies. In fact, many liberal Victorian political thinkers regarded the dissemination of thorough scientific education a sine qua non condition of industrial and human progress. Therefore, education took a rather scientific outlook as Darwinian ideas throve through the educational setting of Britain. Actually, Mill’s concept of education encompassed both the science and the literary studies. Within this context, the purpose of the paper is thus three-fold. First, we intend to validate that Mill’s utilitarian conception of education was different from that of Bentham’s. Even if Mill recognised the necessity to the mental well-being of mankind, his humanistic stance led him to believe “human nature was not a machine to be built after a model.”(Mill, 1997, p. 87) Concurrent with the first aim, we will also describe the changes the national curriculum suffered under the influence of a more scientific outlook, and, lastly, we will put forth Mill’s position on this matter.